Training In Content Creation for Dakwah as Community Service of Faculty of Social Sciences in Women's Dakwah Organizations PC. Pemudi Persis Rancaekek and PC. Persistri Rancaekek In Bandung Regency - Rahman, Mufti fauzi (Universitas INABA, 2023)
The rapid growth of digital content, driven by the increasing penetration of the Internet of Things (IoT), has accelerated access to information through the internet. This phenomenon, coupled with the crucial role of social media, has transformed the function of social media from mere social networking platforms into essential tools in various fields, including Islamic preaching (Dakwah). This community service is carried out and organized by Faculty of Social science Bhakti Kencana University in PC. Pemudi Persatuan Islam (Persis) Rancaekek and PC. Persistri Rancaekek in Bandung Regency, as women's preaching organizations actively using social media as a means of disseminating Islamic messages. The training implementation method involves active community participation in problem-solving with a practical learning approach. Through a regional situation analysis, this training is conducted in stages: preparation, face-to-face implementation, and evaluation of community engagement. The implementation, Community service uses Canva application as a practical platform for creating preaching content. Results and discussions cover the application of preaching content creation practices using Canva. The evaluation of community engagement involves pre-tests and post-tests as measures of training success. The results show that it is quite effective in improving participants’ understanding and skills in using Canva for preaching